2000
DOI: 10.1038/35025203
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis

Abstract: Atherosclerosis, a disease of the large arteries, is the primary cause of heart disease and stroke. In westernized societies, it is the underlying cause of about 50% of all deaths. Epidemiological studies have revealed several important environmental and genetic risk factors associated with atherosclerosis. Progress in defining the cellular and molecular interactions involved, however, has been hindered by the disease's aetiological complexity. Over the past decade, the availability of new investigative tools,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

39
4,015
3
215

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 5,008 publications
(4,272 citation statements)
references
References 70 publications
39
4,015
3
215
Order By: Relevance
“…Indeed, the adherence of circulating monocytes to the endothelial lining of large arteries is one of the earliest detectable events in human and experimental atherosclerosis. It has been proposed that the subsequent transendothelial migration of these adherent monocytes, their accumulation in the intima and transformation into lipid-engorged foam cells result in the formation of atherosclerotic plaques [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the adherence of circulating monocytes to the endothelial lining of large arteries is one of the earliest detectable events in human and experimental atherosclerosis. It has been proposed that the subsequent transendothelial migration of these adherent monocytes, their accumulation in the intima and transformation into lipid-engorged foam cells result in the formation of atherosclerotic plaques [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is regarded as a chronic inflammatory disease that can start at an early age (1) and progress throughout life, causing structural changes in the arterial wall (2). This process is modulated by known risk factors such as dyslipidemia, diabetes, and hypertension, and can result in more prominent arterial wall structural changes in subjects who are at risk for developing cardiovascular disease (3).…”
mentioning
confidence: 99%
“…1 The genetic basis for several Mendelian disorders that can lead to early-onset CAD has been elucidated, exemplified by familial hypercholesterolaemia which is caused by mutations in the low-density lipoprotein receptor gene. 2,3 However, these Mendelian disorders only account for a small percentage of CAD patients. In the majority of cases, the disease is a result of the combined effect of multiple genetic and environmental factors, where each of the genetic factors makes a moderate contribution.…”
mentioning
confidence: 99%
“…In the majority of cases, the disease is a result of the combined effect of multiple genetic and environmental factors, where each of the genetic factors makes a moderate contribution. [2][3][4][5] Recently, a large-scale, genome-wide association study of 65 671 gene-based single nucleotide polymorphisms in relation to myocardial infarction, a severe condition of CAD, was performed in a large group of Japanese cases (n ¼ 1133) and two control groups (n ¼ 1006 and 872, respectively). The study showed a strong association between susceptibility to myocardial infarction and polymorphisms in a 50 kb genomic region on chromosome 6p21 that contains the lymphotoxin-a (LTA) gene.…”
mentioning
confidence: 99%